Valsartan Attenuated Homocysteine-Induced Impaired Autophagy and ER Stress in Human Umbilical Vein Endothelial Cells - Xinyan Wu; Ani Wang; Long Xu; Meng Li; Qingxian Zhai; Weidong Wang; Chunling Li; Lizi Jin (Hindawi-Wiley, 2023)
Hyperhomocysteinemia is a risk factor for various cardiovascular diseases. However, the mechanism underlying homocysteine- (Hcy-) induced vascular injury remains unclear. The purpose of the present study was to examine a potential mechanism by which Hcy induced injury in human umbilical vascular endothelial cells (HUVEC). The protein abundance of autophagy-related markers was markedly decreased after Hcy treatment, which was associated with endoplasmic reticulum (ER) stress and apoptosis in HUVECs. Protein expression level of angiotensin II type 1 receptor (AT1 receptor) was dramatically increased in response to Hcy. Valsartan, an AT1 receptor blocker, improved autophagy and prevented ER stress and apoptosis in HUVECs treated with Hcy. Consistent with this, silence of AT1 receptor with siRNA decreased the protein abundance of ER stress markers, prevented apoptosis, and promoted autophagy in HUVECs. Inhibition or knockdown of AT1 receptor was shown to be associated with suppression of p-GSK3β/GSK3β-p-mTOR/mTOR signaling pathway. Additionally, inhibition of autophagy by 3-MA aggravated Hcy-induced apoptosis, while amelioration of ER stress by 4-PBA prevented Hcy-induced injury in HUVECs. Hcy-induced HUVEC injury was likely attributed to AT1 receptor activation, leading to impaired autophagy, ER stress, and apoptosis.